Breaking bad news in ophthalmology: a literature review - Vasconcellos,Cecília Francini Cabral de (2022)
ABSTRACT Medical specialties have recognized that breaking bad news assists clinical practice by mitigating the impact of difficult conversations. This scenario also encourages various studies on breaking bad news in ophthalmology since certain ocular diagnoses can be considered bad news. Thus, the objective is to review the scientific literature on breaking bad news in ophthalmology. The literature databases like MEDLINE/PUBMED, EMBASE, LILACS, SCOPUS, COCHRANE, and SCIELO, were screened for related research publications. Two independent reviewers read all the articles and short-listed the most relevant ones. Seven articles, in the formats of original article, review, editorial, oral communication, and correspondence, were reviewed. Conclusively it reveals that ophthalmologists are concerned with communicating bad news effectively but lack related studies. Nevertheless, there is a growing realization that training in breaking bad news can increase physicians’ confidence during communication, thus, benefiting the therapeutic relationship with the patient and his family. Therefore, it would be valuable to include breaking bad news training in the curriculum of residencies.